九州西方海域産小型歯鯨類の研究―15 : 日本近海で捕獲されたスナメリの水中音 - Mizue, Kazuhiro; Takemura, Akira; Nakasai, Kei (長崎大学水産学部, 1968)
In Japan, the chinese finless porpoises which had been caught in the Japanese coastal sea are bred in three aquariums, but the underwater sound of this species have not been recognized yet. The authors collected their signals and analyzed them by sound spectorograph in the same way as for the bottlenosed dolphin. 1) Unlike the bottlenosed dolphin, however, this species did not make "Whistle", and "Clicks" of this species were lower than those of the bottlenosed dolphin. 長崎大学水産学部研究報告, v.25, pp.25-32; 1968 departmental bulletin paper